Islandská finanční krize - Rosínová, Ivana (Vysoká škola ekonomická v Praze, 2010)
Diplomová práce se zabývá problematikou finančních krizí, konkrétně analýzou islandské finanční krize v roce 2008. Hlavním cílem práce je popsat průběh, příčiny a důsledky této krize. V teoretické části jsou shrnuty základní poznatky, které se týkají problematiky finančních krizí. Popisná část se zabývá předkrizovým vývojem islandské ekonomiky a průběhem finanční krize. Závěrečná část je věnována analýze islandské finanční krize, pro kterou je využit obecný model systemické finanční krize. The diploma work deals with the problems of financial crises, concretely with the Icelandic financial crisis in 2008. The main target of the work is to describe the course, the causes and the consequences of the financial crisis. The fundamental informations about the financial crises are summarized in the theoretical part. The descriptive part deals with the development of the icelandic economy before crisis and with the course of the financial crisis. The final part is devoted to the analysis of the icelandic financial crisis, for that is used the general model of systemic financial crises.